Women narratives from Tornedalen, northernmost Sweden : gender and culture in perspective - Juntti-Henriksson, Ann-Kristin (Luleå tekniska universitet, Arbetsvetenskap, 2008)
This thesis concerns gender issues based on 103 interviews with women from the northernmost borderland of Sweden (Tornedalen area). The interviews become women narratives as told from their lives, including anecdotes of particular events as well as a vast amount of information related to gender and equality. Feminist poststructuralism inspired me in this thesis. I believe that approaching feminist poststructural theory and practice may help in understanding how the local culture has influenced gender relations in Tornedalen. Each and every woman is unique and shaped by various discourses throughout her life. However, when combining all unique women into a group of women we can see both differences and common characteristics in the group. By drawing on discourse and feminist poststructural analysis I have attempted to convey my understanding of the respondents' narratives. On the one hand, they are very different from each other, and express contradictory views; on the other hand, they have common characteristics that are shared by many women. I believe that it is important to consider all possibilities opened up through feminist poststructural analysis. The thesis comprises six papers which emphasizes different aspects on how women have adapted their lives according to the local culture of Tornedalen. The findings also reflect a historical perspective from the middle to the late twentieth century, including moving from a time when most women were full-time housewives to a time when most women work outside the home. The traditional culture in Tornedalen still existed in the late 1990s with pressure seemingly coming from the older generations to maintain traditional gender functions. Tornedalen women often seem to be preoccupied by imagery of what the local society expects and/or demands of them. Altogether, the knowledge of the participants in this study has produced multiple truths about gender and about women's lives. As would be expected, experiences of the women differed, as did their understandings of ...